A CASE OF COVID-19 PNEUMONIA IN HEMODIALYSIS PATIENT - Stojanoska, Tatjana; Rambabova Bushljetik, Irena; Murtezai, Osman; Taleska Matovska, Natasha; Dimoska Chifligaroska, Elizabeta; Caposka, Olga (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
SARS-CoV-2 (COVID-19) is an infectious disease caused by a novel corona virus that has spread rapidly, resulting in a worldwide pandemic. Even though end-stage renal disease (ESRD) patients are particularly susceptible to COVID-19 infection and can develop severe to critical clinical presentation, there are still limited studies and case reports about COVID-19 in ESRD patients.End-stage renal disease (ESRD) is a severe medical condition with a high prevalence of co-morbid conditions including diabetes, hypertension, and cardiovascular disease.We report case of a 72-years-old woman with ESRD on regular hemodialysis-outpatient, with history of diabetes mellitus type-2 and hypertension, which was positive to COVID-19 and developed pneumonia. She was one of our first registered cases of COVID-19 in our hospital and was successfully cured. Our patient reported symptoms typical of COVID-19, initially, (fever, sweating, weakness, stuffy nose, dry cough and shortness of breath, although she denied contact with infected individuals), but on the day of admission her clinical picture was atypical. She developed a severe clinical picture with the typical presentation of COVID-19 pneumonia on chest X-ray, but without leukopenia as a typical presentation of this disease in her laboratory findings. We describe the clinical presentation of this patient, the diagnostic process, the laboratory and imaging investigations, as well as the course and outcome of treatment. Keywords :  COVID-19, Hemodialysis, Pneumonia, x-ray. https://doi.org/10.55302/JMS 2141022s